2020
DOI: 10.3389/fmicb.2020.533209
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Synergistic Activity of Antimicrobial Combinations Against blaKPC and blaNDM-Producing Enterobacterales With blaIMP or mcr Genes

Abstract: Carbapenemase-producing Enterobacterales have become a severe public health concern because of their rapidly transmissible resistance elements and limited treatment options. The most effective antimicrobial combinations against carbapenemaseproducing Enterobacterales are currently unclear. Here, we aimed to assess the therapeutic effects of seven antimicrobial combinations (colistin-meropenem, colistin-tigecycline, colistin-rifampicin, colistin-erythromycin, meropenem-tigecycline, meropenem-rifampicin, and mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In cases with MDR and XDR infections treatment with combinations of two or more antibiotics is often selected [13] due to potential benefits in lowering the sub-MICs and achieving a synergistic effect [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases with MDR and XDR infections treatment with combinations of two or more antibiotics is often selected [13] due to potential benefits in lowering the sub-MICs and achieving a synergistic effect [35].…”
Section: Discussionmentioning
confidence: 99%
“…Although the in vitro activity of most combinations may be scored as synergistic, their in vivo effectiveness remains uncertain due to the complexity of the infections such as infection site, pharmacokinetic, and pharmacodynamics characteristics of the drugs [13]. The results from genome sequences and epidemiological data of more than 1700 K. pneumoniae samples isolated from patients in 244 hospitals in 32 countries during the European Survey of Carbapenemase-Producing Enterobacteriaceae demonstrate that carbapenemase acquisition is the main cause of CR and 477 of 682 (69.9%) carbapenemase-positive isolates are concentrated in four clonal lineages (11,15, 101, 258/512) and their derivates [36], [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the potential shown with the carbapenem and polymyxin combinations, carbapenem and tigecycline combination studies have yielded fewer promising results against KPCKP. Numerous in vitro studies failed to observe synergistic killing against KPCKP when a carbapenem was paired with tigecycline [41,48,49], whereas other investigations reported that the use of a carbapenem antagonized the killing of tigecycline [50]. Michail et al tested tigecycline drug combinations in vivo using a murine thigh infection model and concluded that the addition of meropenem antagonized the activity of tigecycline against three of the eight KPCKP strains that were investigated, whereas the addition of rifampin or gentamicin increased the killing of KPCKP by tigecycline [41].…”
Section: Klebsiella Pneumoniae 41 K Pneumoniae Carbapenemase-producin...mentioning
confidence: 99%
“…In addition to dual combinations that are composed of a carbapenem and another agent, several triple combinations that utilize two antibacterials and a carbapenem have been evaluated against KPCKP. Triple combinations of a carbapenem, a polymyxin, and either tigecycline or an aminoglycoside were capable of killing more KPCKP than double combinations in multiple in vitro studies [32,33,49]. Dynamic in vitro models have also suggested that synergy against KPCKP may be achieved with the triple combination of a carbapenem, a polymyxin, and rifampin [39,40].…”
Section: Klebsiella Pneumoniae 41 K Pneumoniae Carbapenemase-producin...mentioning
confidence: 99%